Analisis Kinerja Reksadana Saham Syariah Dengan Metode Sharpe Periode 2020-2021 - Dela Leli alya febrianti; Nuriddzati Aisyah; Siti Amaroh (Jurnal Perbankan Syariah, 2023)
The purpose of this study was to analyze the performance of Islamic Stock Mutual Funds using the Sharpe method and to compare the performance of Islamic Stock Mutual Funds with Benchmark performance during the study period. The research method uses descriptive techniques with a quantitative approach. The results of research on the performance of Islamic equity mutual funds using the Sharpe method show that there are Islamic equity mutual funds that consistently outperform the benchmark, namely the Sukuk-Based Bahana Tawqiya Islamic equity mutual fund from PT Bahana TCW Investment Management which has the highest Sharpe ratio based return performance among other mutual funds.